Regional income and employment effects of the 1972 Munich Olympic Summer Games - Stephanie Jasmand; Wolfgang Maennig (University of Hamburg, Faculty of Business, Economics and Social Sciences, Chair for Economic Policy, 2007)
Olympic Games may have impacts on income and employment in the host city, but no ex post study has been carried out for European Olympic host cities to date. The present study closes this gap using the 1972 Munich Olympic Games. The data period examined in this study allows for analysis of long-term effects. In addition, the methodology avoids overestimating the significance of the effects. Finally, we report results for all possible combinations of pre- and post-Olympic periods. The results: income in Olympic regions grew significantly faster than in other German regions. In contrast, no employment effects were identified.
Keywords: L83; O18; R11; R53; R58; 330; Olympic Games; mega events; income; employment